Degenerate four-wave mixing in n-Ge due to intervalley redistribution of hot electrons - Vasetskii, V.M.; Poroshin, V.N.; Ignatenko, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
We have studied backward degenerate four-wave mixing at CO₂ laser wavelengths in n-type Ge. Phase conjugation due to redistribution of free electrons between equivalent valleys was observed. The effect is related to carrier heating by infrared radiation.